2018
DOI: 10.1016/j.cmi.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

How to isolate, identify and determine antimicrobial susceptibility of anaerobic bacteria in routine laboratories

Abstract: The present review aims to update and improve anaerobic microbiology in laboratories with optimal conditions as well as encourage its routine implementation in laboratories with restricted resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 54 publications
(51 reference statements)
2
83
0
21
Order By: Relevance
“…In vivo studies highlight links between the long-term microbiota compositional changes and host dysbiosis, including the development of allergic, metabolic, immunological and inflammatory diseases 5-8,10,11,19-21 . While uncovering the direct effects of different antibiotics on our gut flora is critical to improve general health, technical difficulties hamper routine testing of antibiotic susceptibility in anaerobes 22,23 . Currently available data on bacterial susceptibility to antibiotics is focused on invasive pathogens and offers little to no resolution in the diversity of the human gut microbiota 24 .…”
Section: Main Textmentioning
confidence: 99%
“…In vivo studies highlight links between the long-term microbiota compositional changes and host dysbiosis, including the development of allergic, metabolic, immunological and inflammatory diseases 5-8,10,11,19-21 . While uncovering the direct effects of different antibiotics on our gut flora is critical to improve general health, technical difficulties hamper routine testing of antibiotic susceptibility in anaerobes 22,23 . Currently available data on bacterial susceptibility to antibiotics is focused on invasive pathogens and offers little to no resolution in the diversity of the human gut microbiota 24 .…”
Section: Main Textmentioning
confidence: 99%
“…The miscellaneous colonies on the three-culture media at the primary isolation were sub cultured and characterized by phenotypic features, cultural and cellular morphology by gram stain depending on the rules of Nagy et al, (2018) for the identification of anaerobic clinical isolates. Molecular amplification, LAMP technique was used to confirm bacterial species.…”
Section: Identification Of the Bacterial Isolatesmentioning
confidence: 99%
“…Rapid identification kits e.g. API systems and VITEK MS-bioMérieux system require high dense inoculum which is difficult with the slow growing periodontal bacteria, also many anaerobes are non-reactive in biochemical tests and there is no available data base for each type of periodontal pathogens (Nagy et al, 2018;Garner et al, 2014). Therefore, most laboratory identification methods shifted from classical biochemical methods to the most potent identifier one, 16SrRNAtargeted molecular technique that overcomes limitations of culture depended-identification methods (wade, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports on anaerobic infections worldwide, and it has been demonstrated that antibiotics in the current market have reduced the efficacy against anaerobic bacterial infection (5). Antimicrobial resistance among anaerobes is increasing dramatically due to changes in the drug resistance mechanisms (6). Metronidazole is a broad-spectrum antibiotic for anaerobic infections.…”
Section: Introductionmentioning
confidence: 99%